PHYSICAL QUALITY OF PRIMARY SCHOOL STUDENTS AND METHODS OF THEIR DEVELOPMENT (Scientific journal of the Fergana State University, 2025)
This article is dedicated to the issues of developing strength and physical qualities of primary school students. The research provides an in-depth analysis of children's age-specific physical development characteristics, methodology for forming strength qualities, and pedagogical approaches.